2021
DOI: 10.1136/bmjopen-2020-042364
|View full text |Cite
|
Sign up to set email alerts
|

Role of locoregional surgery in treating FIGO 2009 stage IVB cervical cancer patients: a population-based study

Abstract: ObjectiveWe aimed to analyse the clinical value of primary site surgery in improving the cancer-specific survival (CSS) and overall survival (OS) of initial metastatic cervical cancer patients.DesignA population-based retrospective study.SettingNational Cancer Institute’s Surveillance, Epidemiology and End Results database.ParticipantsWe analysed 1390 patients with the International Federation of Gynecology and Obstetrics 2009 stage IVB cervical cancer with complete clinical data treated between 2010 and 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…This study also provides additional insights regarding the factors that impact the utilization of IMT in patients with stage IVB cervical cancer compared with prior studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 19 , 21 , 24 , 25 , 30 , 48 , 49 , 50 , 51 , 52 , 53 ]. We found that patients with Medicaid insurance or no insurance, older age, or either distant lymph node or distant organ metastasis but not with both, and those treated at Non-Academic/Research Facilities or with CT + EBRT ± ICBT were significantly less likely to receive IMT.…”
Section: Discussionmentioning
confidence: 78%
“…This study also provides additional insights regarding the factors that impact the utilization of IMT in patients with stage IVB cervical cancer compared with prior studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 19 , 21 , 24 , 25 , 30 , 48 , 49 , 50 , 51 , 52 , 53 ]. We found that patients with Medicaid insurance or no insurance, older age, or either distant lymph node or distant organ metastasis but not with both, and those treated at Non-Academic/Research Facilities or with CT + EBRT ± ICBT were significantly less likely to receive IMT.…”
Section: Discussionmentioning
confidence: 78%
“…Lastly, animal models indicated that reducing the cells in the core lesion via radical topical therapy might reverse tumor-associated immunosuppression [25]. There is now increasing evidence showing that the local treatment (radiotherapy or surgery) of the primary lesion could prolong the survival of metastatic cervical cancer [26][27][28][29][30][31] and decrease the mortality rate by nearly 30%, the median survival was 3 to 4 months longer [26,27,32]. However, surgery might not be suitable for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration can be given to resection of metastatic foci on a case-by-case basis, depending on factors such as the presence of symptoms, number of metastatic foci, feasibility of treatment, and response to chemotherapy. Primary site surgery has also been shown to improve survival of patients with non-visceral distant metastasis 10…”
Section: Role Of Surgery In Locally Advanced Cervical Cancermentioning
confidence: 99%
“…Primary site surgery has also been shown to improve survival of patients with non-visceral distant metastasis. 10…”
Section: Role Of Surgery In Metastatic Cervical Cancer (Stage Ivb)mentioning
confidence: 99%